Réponses

Meilleure réponse !
2014-03-23T18:58:25+01:00
Exercice 60
g(3) =7=3a+b
g(9) =11=9a+b

b=11-9a  on remplace danns l'autre 3a+11-9a=7
                                                           -6a=7-11
                                                             6a=4
                                                             a=4/6=2/3

 et b = 11-9a
     b= 11-9x2/3
     b= 11-3x3x2/3
     b=11-6
     b=5,       ,et g(x) = 2x/3+5

Exercice 62

i(-1)=2=-a+b    b=2+a
i(3)=2=3a+b on remplace b par son expression 3a+2+a=2
                                                                             4a=2-2
                                                                             4a=0
                                                                                a=0
b=2+a=2
i(x)=2